High Prevalence of Antibiotic Resistance among Opportunistic Pathogens Isolated from Patients with COVID-19 under Mechanical Ventilation: Results of a Single-Center Study - Chiara Temperoni; Luca Caiazzo; Francesco Barchiesi (MDPI AG, 2021)
The effect of the COVID-19 pandemic on antibiotic resistance diffusion in healthcare settings has not been fully investigated. In this study we evaluated the prevalence of antibiotic resistance among opportunistic pathogens isolated from patients with COVID-19 under mechanical ventilation. An observational, retrospective, analysis was performed on confirmed cases of COVID-19 patients who were admitted to the ICU department of San Salvatore Hospital in Pesaro, Italy, from 1 February 2021 to 31 May 2021. We considered all consecutive patients aged ≥ 18, under mechanical ventilation for longer than 24 h. Eighty-nine patients, 66 (74.1%) men and 23 (25.9%) women, with a median age of 67.1 years, were recruited. Sixty-eight patients (76.4%) had at least one infection, and 11 patients (12.3%) were colonized, while in the remaining 10 patients (11.2%) neither colonization nor infection occurred. In total, 173 microorganisms were isolated. There were 73 isolates (42.2%) causing bacterial or fungal infections while the remaining 100 isolates (57.8%) were colonizers. Among Gram-negative bacteria, E. coli, A. baumannii and K. pneumoniae were the most common species. Among Gram-positive bacteria, S. aureus and E. faecalis were the most common species. Overall, there were 58/105 (55.2%) and 22/59 (37.2%) MDR isolates among Gram-negative and Gram-positive bacteria, respectively. The prevalence of an MDR microorganism was significantly higher in those patients who had been exposed to empiric antibiotic treatment before ICU admission. In conclusion, we found a high prevalence of antibiotic resistance among opportunistic pathogens isolated from patients with COVID-19 under mechanical ventilation.